Ontogeny of vocal rhythms in harbor seal pups: an exploratory study. Issue 1 (7th July 2018) - Ravignani, Andrea; Kello, Christopher T; de Reus, Koen; Kotz, Sonja A; Dalla Bella, Simone; Méndez-Aróstegui, Margarita; Rapado-Tamarit, Beatriz; Rubio-Garcia, Ana; de Boer, Bart
Abstract: Puppyhood is a very active social and vocal period in a harbor seal's life Phoca vitulina . An important feature of vocalizations is their temporal and rhythmic structure, and understanding vocal timing and rhythms in harbor seals is critical to a cross-species hypothesis in evolutionary neuroscience that links vocal learning, rhythm perception, and synchronization. This study utilized analytical techniques that may best capture rhythmic structure in pup vocalizations with the goal of examining whether (1) harbor seal pups show rhythmic structure in their calls and (2) rhythms evolve over time. Calls of 3 wild-born seal pups were recorded daily over the course of 1–3 weeks; 3 temporal features were analyzed using 3 complementary techniques. We identified temporal and rhythmic structure in pup calls across different time windows. The calls of harbor seal pups exhibit some degree of temporal and rhythmic organization, which evolves over puppyhood and resembles that of other species' interactive communication. We suggest next steps for investigating call structure in harbor seal pups and propose comparative hypotheses to test in other pinniped species.